The Lobamba interpretation centre of the oral arts and landscape. - Wilcox, Afua (My University, 2014)
There is a rich inventory of the oral arts within Swazi culture. In a culture that relies heavily on annual events saturated with song, dance and praise poetry lies the opportunity for people to express themselves more freely than within more conservative dialogue. Swaziland has a lack of freedom of expression in casual conversation and media. Many people fear for the harm that might come to them if they speak out of turn. But there is a new generation full of burning questions towards culture, a youth that has access to most international information through the internet, cellphones and television and yet struggles to get the answers they need from Swazi culture. Many boundaries within Swazi culture are caused through respect for powers of a spiritual nature and love of King. However there are few opportunities for the youth of Swaziland to voice their concerns and ask the questions that would help them affi liate more closely to Swazi tradition. The Lobamba Interpretation Centre of the Oral Arts and Landscape explores the possible solution of a forum that enables the youth to interact with their culture, to unearth the ghosts of the past on a more regular basis through the medium of the arts, a medium they have become familiar with due to technology. The oral arts of storytelling, poetry and song are a neutralized means of communication and an opportunity for dialogue in a respectful and entertaining way that can still bring forth a message without disrespecting the cultural element of speech, essentially using culture to answer cultural issues. Politics is always controversial but the arts allows for the disparity and a layering of opinion. This thesis is in no way a critique of Swazi culture, it merely aims to source solutions from Swazi culture to accommodates dialogue and freedom of speech in a growing Swazi society. It aims to understand the importance of performance, a language familiar to the people of Swaziland. It unearths examples of traditional Swazi methods of communication that have been used for centuries, in order to include a younger generation that is very heavily reliant on international customs due to their accessibility to the media, a media that embraces global news but shies away from the bigger issues behind culture. Swazi culture and landscape form a tight bond .The Swazi are a people of their land who listen and base many of their cultural decisions on natural vegetation, weather, river sources and topography. In order to fully embrace Swazi culture and expression, one must also begin to understand the dialogue between Swazi culture and landscape. My building is an interpretation centre of the oral arts in Lobamba, Swaziland, the heart of Swazi culture. My building suggests the opportunity of a site that allows for a freedom of expression in the very heart of these tensions, without disrupting /disrespecting the cultural norms of its context. This will be programmed with a series of platforms for expression, stages and exhibition spaces that can allow for connection points between the youth and culture.The building will house an exhibition space for the oral arts as well as accommodation for the infl ux and subsequent dispersal of people that take part in cultural ceremonies through pilgrimages 4 times a year. My thesis allows for a discovery of this complex and layered landscape, an unpacking of time, landscape and space and refl ects back its impact on Swazi culture and the oral arts namely: storytelling, song and praise poetry. It also documents the existing built form and topography and begins to make sense of the area’s patterning. It builds an understanding of the oral arts and its importance in Swazi context in order to sustain the notion of tradition. In this book, I will be taking you on a journey through my thought process towards the interpretation center of the oral arts and landscape. All quoted poetry within this book is my own work that I have marked with “inverted commas”.
Keywords: City planning--Swaziland--History; Lobamba (Swaziland)--Buildings, structures, etc.; Architecture, Modern--21st century--Swaziland--Lobambo